Detection and evolutionary analysis of picobirnaviruses in treated wastewater. Issue 3 (27th December 2014) - Zhang, Shiwei; Bai, Ru; Feng, Run; Zhang, Hongxun; Liu, Lixin
Summary Wastewater contains numerous viruses. In this study, picobirnaviruses (PBVs) were detected in the stream of a wastewater treatment plant in Changsha, Hunan province, China, and evolutionary analysis of the isolated PBVs was performed. The phylogenetic tree revealed that the PBVs were highly divergent and could be classified into six distinct groups according to their hosts. Among these groups, pairwise comparison of the six groups revealed that the nucleotide distance of group 4 (bootstrap value = 0.92; nucleotide identity = 94%) was the largest. Thus, group 4 might represent a new division of PBVs. Comprehensive analysis of the obtained PBV sequences to investigate their evolutionary history and phylodynamics revealed that group 5 (PBVs from monkey) exhibited maximum polymorphism (K = 30.582, S = 74, η = 98, Pa = 47) and lowest nucleotide substitutions per site per year (6.54E‐3 subs per site per year), except group 4. Maximum clade credibility tree indicated that group 5 appeared earlier than the other groups. In conclusion, this study detected PBVs in treated wastewater in China, and identified a new PBV group. Furthermore, among these PBVs, group 5 was found to survive longer and present a balance between PBVs and their monkey host.